Zn-regulated GTPase metalloprotein activator 1 modulates vertebrate zinc homeostasis - Weiss, Andy; Murdoch, Caitlin C; Edmonds, Katherine A; Jordan, Matthew R; Monteith, Andrew J; Perera, Yasiru R; Rodríguez Nassif, Aslin M; Petoletti, Amber M; Beavers, William N; Munneke, Matthew J; Drury, Sydney L; Krystofiak, Evan S; et al. (Cell, 2022)
Zinc (Zn) is an essential micronutrient and cofactor for up to 10% of proteins in living organisms. During Zn limitation, specialized enzymes called metallochaperones are predicted to allocate Zn to specific metalloproteins. This function has been putatively assigned to G3E GTPase COG0523 proteins, yet no Zn metallochaperone has been experimentally identified in any organism. Here, we functionally characterize a family of COG0523 proteins that is conserved across vertebrates. We identify Zn metalloprotease methionine aminopeptidase 1 (METAP1) as a COG0523 client, leading to the redesignation of this group of COG0523 proteins as the Zn-regulated GTPase metalloprotein activator (ZNG1) family. Using biochemical, structural, genetic, and pharmacological approaches across evolutionarily divergent models, including zebrafish and mice, we demonstrate a critical role for ZNG1 proteins in regulating cellular Zn homeostasis. Collectively, these data reveal the existence of a family of Zn metallochaperones and assign ZNG1 an important role for intracellular Zn trafficking.